Trade associations as a tool for implementation of collusive agreements - Juppet Ewing, María Fernanda (Derecho Público Iberoamericano, 2017)
This article seeks to review the way in which trade associations are instrumentalized for the realization of collusive agreements. Distinguishing two main functions in the cases studied in Chile. First, a control tool of the members of the agreement. And, secondly, a way of equating the power of health care providers. Finally, this article comment on some jurisprudential views of the TDLC regarding trade associations.